Performance of existing water treatment plants of Kathmandu valley - Kansakar, Bhagwan Ratna (Nepalese Journal of Engineering, 2005)
There are seven existing water supply systems, namely, Balaju, Bansbari, Sundarijal, Bhaktapur, Dudhpokhari, Shainbu and Chapagaon that supply water to the various parts of the Kathmandu valley. The water drawn from the water source is not suitable for drinking purpose without treatment. The water treatment has been carried out in all the existing water supply systems. Treatment varies from bleaching powder chlorination in Chapagaon system to conventional treatments like sedimentation, filtration and chlorination in Bansbari and Sundarijal systems. The status of the existing water treatment plants has been studied in detail. The study showed that most of the water treatment plants are in poor condition and very poorly maintained. Besides, the operational data are not properly recorded and kept. The treated water quality deteriorates in rainy season and does not appear to be suitable for drinking as per WHO guideline. The maintenance personnel are not well trained to operate and maintain the treatment plants. The maintenance budget is too low for normal maintenance of the treatment plants. Among the existing water treatment plants, the Mahankalchaur water treatment plant is working most satisfactorily. Keywords: water supply systems, water quality, turbidity, surface water and groundwater Nepalese Journal of Engineering Vol.1(1) 2005 pp.18-24